2014
DOI: 10.1007/s12032-014-0359-z
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of glypican-3 as a prognostic marker in HCC using X-tile software

Abstract: Glypican-3 (GPC3) is a widely used immunohistochemical marker for hepatocellular carcinoma (HCC); however, its prognostic value is unclear. Immunohistochemical evaluation of GPC3 expression was performed on 300 postoperative HCC tissue samples with paired adjacent non-tumor tissues on tissue microarray sections. The integral optic density, representing the expression level of GPC3 in each HCC sample, was calculated using Image-Pro Plus. The outcome-based cut-point optimization was performed using X-tile softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 19 publications
3
28
0
1
Order By: Relevance
“…In this study, we demonstrate that regardless of the expression pattern, the presence of GPC3 expression was associated with more frequent AFP elevation, microvascular invasion, and hepatic causes of death, suggestive of a more aggressive behavior in GPC3-positive HCCs. These results are in line with previous reports that have associated GPC3 positivity with vascular invasion and AFP elevation (12,(15)(16)(17). When the pattern of GPC3 staining was taken into account, we found that the cases with diffuse GPC3 expression were associated with younger age (although marginally significant), higher serum AFP levels, and more frequent microvascular invasion compared with HCCs with focal GPC3 expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we demonstrate that regardless of the expression pattern, the presence of GPC3 expression was associated with more frequent AFP elevation, microvascular invasion, and hepatic causes of death, suggestive of a more aggressive behavior in GPC3-positive HCCs. These results are in line with previous reports that have associated GPC3 positivity with vascular invasion and AFP elevation (12,(15)(16)(17). When the pattern of GPC3 staining was taken into account, we found that the cases with diffuse GPC3 expression were associated with younger age (although marginally significant), higher serum AFP levels, and more frequent microvascular invasion compared with HCCs with focal GPC3 expression.…”
Section: Discussionsupporting
confidence: 92%
“…A recent review (4) attributed the large range of survival to differences in HCC staging. Our own case series included patients who underwent various anti-cancer treatments such as TACE and RFA, while some prognostic studies enrolled patients with no prior treatment (15,18). However, we did not find Determined by log-rank test for comparison of overall survival and disease-free survival between GPC3-positive and GPC3-negative group.…”
Section: Discussionmentioning
confidence: 86%
“…HRs and its 95% CIs of OS and DFS were extracted from all included articles or calculated indirectly by the methods described above. Initial treatment for patients with HCC with surgical resection was performed in 11 studies [ 18 22 , 26 29 , 31 , 35 ] and liver transplantation (LT) in 1 article. [ 30 ] The scope of sample size in all studies varies from 31 to 362.…”
Section: Resultsmentioning
confidence: 99%
“…An optimal cutoff value for the IHC score that separates patients into low and high CNPY2 isoform2 expression groups with respect to OS was determined using X-tile software (version 3.6.1; Yale University, New Haven, CT, USA) at the largest chi-square value in the training cohort, as described previously[ 25 , 26 ]. Categorical variables are presented as percentages, and they were compared using the chi-square test or Fisher's exact test.…”
Section: Methodsmentioning
confidence: 99%